2020
DOI: 10.1044/2020_ajslp-19-00168
|View full text |Cite
|
Sign up to set email alerts
|

Children's English Consonant Acquisition in the United States: A Review

Abstract: Purpose Speech-language pathologists' clinical decision making and consideration of eligibility for services rely on quality evidence, including information about consonant acquisition (developmental norms). The purpose of this review article is to describe the typical age and pattern of acquisition of English consonants by children in the United States. Method Data were identified from published journal articles and assessments reporting English conson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 58 publications
1
25
0
2
Order By: Relevance
“…It would be useful to examine underspecification in younger children to see if TD children demonstrate Stage I at an earlier age than children with PD, and to see if there could be an even earlier stage that we could not identify with our present population and age groups. Moreover, examining underspecification in older children who have theoretically acquired all of their speech sounds (McLeod and Crowe, 2018;Crowe and McLeod, 2020) could provide information about how and when adult-like phonological knowledge is acquired.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be useful to examine underspecification in younger children to see if TD children demonstrate Stage I at an earlier age than children with PD, and to see if there could be an even earlier stage that we could not identify with our present population and age groups. Moreover, examining underspecification in older children who have theoretically acquired all of their speech sounds (McLeod and Crowe, 2018;Crowe and McLeod, 2020) could provide information about how and when adult-like phonological knowledge is acquired.…”
Section: Limitationsmentioning
confidence: 99%
“…As a result, children are predicted to first acquire the least specified phonemes, and more specified phonemes are added over time as features are defined and categorized. Thus, American English-speaking children are expected to produce phonemes with 90% accuracy by the following ages: 2;11 (years; months)-/p b d m n h w/; 3;11-/t k gη f j/ 4;11-/v s z S Ù Ã l/; 5;11-/ ź D ô/; and 6;11-/θ/ (Crowe and McLeod, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These results are similar to those of a previous study that described types of consonant errors in Korean-speaking children between the ages of 3 and 5 years, in which the authors observed that speech sound errors were the most frequent in the order of onset-fricative, nucleus-fricative, and onset-liquid [28]. In English, the easy pronunciation of / m/, /n/, /h/, and /w/, among others is completed first, and alveolar fricatives such as /s/, /sh/, /ch/, /th/, /z/ and liquids (/l/ and /r/) develop later [29,30]. Therefore, researchers have concluded that the maturation of fricative-related pronunciation is slower, and comparisons between children with SSDs and TD may show similar tendencies regardless of the language.…”
Section: Discussionmentioning
confidence: 99%
“…With all its different dialects, the development of English speech sounds differs from other languages. Comparing it to the Arabic language, previous research [3][4][5][6][7] also clarified the difference in the age and order of acquisition of the English speech sounds from those of the Arabic language among its different dialects [8][9][10], Table 1.…”
Section: Introductionmentioning
confidence: 87%